Transcriptome sequencing reveals maelstrom as a novel target gene of the terminal system in the red flour beetle Tribolium castaneum - Pridöhl, Fabian; Weißkopf, Matthias; Koniszewski, Nikolaus; Sulzmaier, Andreas; Uebe, Steffen; Ekici, Arif Bülent; Schoppmeier, Michael (Development, 2017)
Terminal regions of the Drosophila embryo are patterned by the localized activation of the Torso-RTK pathway, which promotes the downregulation of Capicua. In the short-germ beetle Tribolium, the function of the terminal system appears to be rather different, as the pathway promotes axis elongation and, in addition, is required for patterning the extra-embryonic serosa at the anterior. Here, we show that Torso signalling also induces gene expression by relieving Capicua-mediated repression in Tribolium Given that the majority of Torso target genes remain to be identified, we established a differential gene-expression screen. A subset of 50 putative terminal target genes was screened for functions in early embryonic patterning. Of those, 13 genes show early terminal expression domains and also phenotypes were related to terminal patterning. Among others, we found the PIWI-interacting RNA factor Maelstrom to be crucial for early embryonic polarization. Tc-mael is required for proper serosal size regulation and head morphogenesis. Moreover, Tc-mael promotes growth-zone formation and axis elongation. Our results suggest that posterior patterning by Torso may be realized through Maelstrom-dependent activation of posterior Wnt domains.
EVALuna2:9357